The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1128/jcm.34.5.1086-1090.1996
|View full text |Cite
|
Sign up to set email alerts
|

Ribotype diversity of Listeria monocytogenes strains associated with outbreaks of listeriosis in ruminants

Abstract: Ribotyping is a molecular method for the characterization, identification, and typing of bacterial isolates that has value in epidemiological studies. To demonstrate the utility of this technique for typing of Listeria monocytogenes, four outbreaks of epizootic listeriosis in ruminants were investigated through coordinated detection and characterization methods utilizing classical microbiology and nucleic acid-based techniques. L. monocytogenes strains isolated from clinical samples and the silage consumed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…Listeria monocytogenes is such a bacterium. In addition, L. monocytogenes lives naturally in plant and soil environments, and poorly fermented silage often contains high numbers of L. monocytogenes (21,24,58). Outbreaks from raw vegetables that had been fertilized with sheep manure have been documented, as have infections associated with consumption of unpasteurized dairy products and with ice cream that had been infected during processing (23,38,55).…”
Section: Monocytogenesmentioning
confidence: 99%
“…Listeria monocytogenes is such a bacterium. In addition, L. monocytogenes lives naturally in plant and soil environments, and poorly fermented silage often contains high numbers of L. monocytogenes (21,24,58). Outbreaks from raw vegetables that had been fertilized with sheep manure have been documented, as have infections associated with consumption of unpasteurized dairy products and with ice cream that had been infected during processing (23,38,55).…”
Section: Monocytogenesmentioning
confidence: 99%
“…Especially in sheep, listeriosis leads to head tilt and permanent circling movement (Radostits et al., 1999). A L. monocytogenes ‐associated epidemic in cattle and sheep leading extensively to abortion, septicaemia and central nervous symptoms have been rarely reported (Low and Renton, 1985; Wiedmann et al., 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that serotypes 1 ⁄ 2a, 1 ⁄ 2b, 1 ⁄ 2c and 4b are responsible for 95-98% of listeriosis cases (Liu 2006). Among these, serotype 4b strains are isolated mostly from epidemic outbreaks (Raybourne 2002;Borucki and Call 2003), whereas 1 ⁄ 2a, 1 ⁄ 2b and 1 ⁄ 2c are linked to sporadic infections and are the most prevalent serotypes in foods and food production environments (Wiedmann et al 1996). The conventional serological test has become widely used, because it is relatively convenient to perform, but lack of specificity and sensitivity and its low discriminatory ability do not always provide sufficient information in epidemiological investigations (Borucki and Call 2003;Doumith et al 2004).…”
mentioning
confidence: 99%